“That Line Just Kept Moving”: Motivations and Experiences of People Who Use Methamphetamine - Callan Elswick Fockele; Sophie C. Morse; Jenna van Draanen; Sarah Leyde; Caleb Banta-Green; Ly Ngoc Huynh; Alina Zatzick; Lauren K. Whiteside (Western Journal of Emergency Medicine, 2023)
Introduction: Methamphetamine use is on the rise with increasing emergency department (ED) visits, behavioral health crises, and deaths associated with use and overdose. Emergency clinicians describe methamphetamine use as a significant problem with high resource utilization and violence against staff, but little is known about the patient’s perspective. In this study our objective was to identify the motivations for initiation and continued methamphetamine use among people who use methamphetamine and their experiences in the ED to guide future ED-based approaches. Methods: This was a qualitative study of adults residing in the state of Washington in 2020, who used methamphetamine in the prior 30 days, met criteria for moderate- to high-risk use, reported recently receiving care in the ED, and had phone access. Twenty individuals were recruited to complete a brief survey and semi-structured interview, which was recorded and transcribed prior to being coded. Modified grounded theory guided the analysis, and the interview guide and codebook were iteratively refined. Three investigators coded the interviews until consensus was reached. Data was collected until thematic saturation. Results: Participants described a shifting line that separates the positive attributes from the negative consequences of using methamphetamine. Many initially used methamphetamine to enhance social interactions, combat boredom, and escape difficult circumstances by numbing the senses. However, continued use regularly led to isolation, ED visits for the medical and psychological sequelae of methamphetamine use, and engagement in increasingly risky behaviors. Because of their overwhelmingly frustrating experiences in the past, interviewees anticipated difficult interactions with healthcare clinicians, leading to combativeness in the ED, avoidance of the ED at all costs, and downstream medical complications. Participants desired a non-judgmental conversation and linkage to outpatient social resources and addiction treatment. Conclusion: Methamphetamine use can lead patients to seek care in the ED, where they often feel stigmatized and are provided little assistance. Emergency clinicians should acknowledge addiction as a chronic condition, address acute medical and psychiatric symptoms adequately, and provide positive connections to addiction and medical resources. Future work should incorporate the perspectives of people who use methamphetamine into ED-based programs and interventions.